2015
DOI: 10.1002/bmc.3640
|View full text |Cite
|
Sign up to set email alerts
|

Preparative purification of plasmin activity stimulating phenolic derivatives from Gastrodia elata using centrifugal partition chromatography

Abstract: Gastrodia rhizome, a dried and steamed tuber of Gastrodia elata Blume (Orchidaceae), has been traditionally used in Korea, China and Japan for the treatment of neurological and nervous disorders such as headaches, dizziness, vertigo and convulsive illnesses. The ethyl acetate and water extracts of G. elata stimulated plasmin activity. The active ethyl acetate fraction was subjected to centrifugal partition chromatography (CPC) with a two-phase solvent system, composed of n-hexane-ethyl acetate-methanol-water (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…The UV spectrum showed absorption maxima at 221. . By comparing the above results and the previously reported spectroscopic data [38][39][40]42], compound 10 was identified as tris [4-(β-D-glucopyranosyloxy)benzyl] citrate, namely, parishin or parishin A (Figure 4). Parishin A has only been found in G. elata rhizome [38][39][40]42] and Vanda parishii [43].…”
Section: Isolation and Structure Elucidation Of Parishin-related Comp...supporting
confidence: 62%
See 1 more Smart Citation
“…The UV spectrum showed absorption maxima at 221. . By comparing the above results and the previously reported spectroscopic data [38][39][40]42], compound 10 was identified as tris [4-(β-D-glucopyranosyloxy)benzyl] citrate, namely, parishin or parishin A (Figure 4). Parishin A has only been found in G. elata rhizome [38][39][40]42] and Vanda parishii [43].…”
Section: Isolation and Structure Elucidation Of Parishin-related Comp...supporting
confidence: 62%
“…4). Parishin B was identified previously in the G. elata rhizome [39][40][41][42]. These results suggest that the MT twig contained large amount of gastrodin, parishin A and parishin B.…”
Section: Isolation and Structure Elucidation Of Parishin-related Comp...supporting
confidence: 58%
“…Furthermore, phytochemical studies of G. elata have validated that the presence of phenolic compounds in G. elata , for example, p -hydroxybenzyl alcohol (HA), gastrodin (GA) and parishins compounds have been given rise to more attentions because of their pharmacological features [ 14 , 15 ], it is inappropriate to choose only several specific components as essential criteria. Although many efforts have been endeavored to the quality evaluation of G. elata [ 16 , 17 , 18 ], further exploration is still required.…”
Section: Introductionmentioning
confidence: 99%
“…Although many efforts have been endeavored to the quality evaluation of G. elata [ 16 , 17 , 18 ], further exploration is still required. Numerous studies have revealed that the phenolic compounds content (PCC) in G. elata is an important quality index when evaluating its medicinal efficacy [ 15 , 17 , 19 ]. For this application, the correlation between the phenolic compounds content in G. elata and NIRS was also developed, we explore synergy interval partial least squares (Si-PLS) to provide predictive models of PCC by selecting different subintervals.…”
Section: Introductionmentioning
confidence: 99%
“…Li and Jeon et al. were only able to purify gastrodin and liposoluble constituents from tianma extract using HSCCC . To date, an HSCCC method for purification of parishins has not been established.…”
Section: Introductionmentioning
confidence: 99%